Wittgenstein and the philosophy of mind - Ellis, Jonathan; Guevara, Daniel (New York ; Oxford : Oxford University Press, 2013)
In the essays collected here, some of the most influential figures in contemporary philosophy discuss the significance of Wittgenstein's philosophy for understanding the mind.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Wittgenstein, Ludwig, -- 1889-1951 -- Congresses; Philosophy of mind -- Congresses